PENGARUH FAKTOR MOTIVASI KEWIRAUSAHAAN DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT KEWIRAUSAHAAN MAHASISWA FAKULTAS EKONOMI MANAJEMEN UNIVERSITAS NUSA NIPA MAUMERE - Antonius Philipus Gheta; Nunsio Handrian Meylano (Distribusi - Journal of Management and Business, 2022)
The way that can reduce unemployment is by entrepreneurship. Entrepreneurship can also help increase domestic income through the tax sector. Before increasing the number of entrepreneurs and reducing the unemployment rate in Indonesia, the community must be made aware of the importance of increasing entrepreneurship interest. Interest can be interpreted as a sense of pleasure or interest in something. Interest basically cannot be imposed on oneself, for interest is a right for every human being. Factors that influence entrepreneurship interest according to Bygrave in (Buchari, 2011: 11) include personal, environmental and sociological. This research aims to find out the influence of entrepreneurship motivation factors and entrepreneurial knowledge on the entrepreneurial interests of students of the Faculty of Economics Management Study Program, University of Nusa Nipa. The study used a sample of 100 management economics students who had received entrepreneurship courses. Data processing and analysis use multiple regressions. The results showed that partially the motivation variables had a significant effect on entrepreneurship interests and knowledge variables had no significant effect on entrepreneurship interests. While simultaneously the variables of motivation and knowledge significantly affect entrepreneurship interests.